Analysis of Theory of Planned Behavior and Fraud Triangle Theory (Case Study On Sharia Banking) - Nadin, Nadin; Wijayanti, Rahma (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The aim of this research is to test whether attitudes, subjective norms, behavioral control, pressure and opportunities influence the interest of staff in Sharia Banking to commit fraud. The survey was conducted on a sample of 35 sharia banking staff. The research results show that attitudes and pressure influence the interest of Sharia Banking staff to commit acts of fraud, while Subjective Norms, Behavioral Control, and Opportunity do not influence the interest of Sharia Banking staff to commit acts of fraud.